EARLY POST-OPERATIVE PERINEAL WOUND COMPLICATIONS IN PATIENTS UNDERGOING EXTRA LEVATOR ABDOMINOPERINEAL EXCISION, A RETROSPECTIVE STUDY AT DEPARTMENT OF SURGICAL ONCOLOGY - Aun Jamal; Sadaf Batool; Ihtisham Ul Haq; Jibran Mohsin; Osama Shakeel; Shahid Khattak; Aamir Ali Syed (Pakistan Armed Forces Medical Journal, 2020)
Objective: To emphasize on the early wound complications of the above-mentioned procedure.